2012
DOI: 10.1161/circresaha.112.274035
|View full text |Cite
|
Sign up to set email alerts
|

Functional Na V 1.8 Channels in Intracardiac Neurons

Abstract: Rationale:The SCN10A gene encodes the neuronal sodium channel isoform Na V 1.8. Several recent genome-wide association studies have linked SCN10A to PR interval and QRS duration, strongly suggesting an as-yet unknown role for Na V 1.8 in cardiac electrophysiology.Objective: To demonstrate the functional presence of SCN10A/Nav1.8 in intracardiac neurons of the mouse heart. Methods and Results: Immunohistochemistry on mouse tissue sections showed intense Na V 1.8 labeling in dorsal root ganglia and intracardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 31 publications
(33 reference statements)
2
88
0
Order By: Relevance
“…Gating properties were also changed under A‐803467 with hyperpolarized steady‐state inactivation and delayed recovery from inactivation. Interestingly, the left‐shifted steady‐state inactivation was quite consistent with the effect of A‐803467 in isolated mouse intracardiac neurons delineated by Verkerk et al 36. Like other sodium channel blockers, our results support that A‐803467 might block sodium channels in an inactivated state and the number of trapped inactivated sodium channels might be increased during repeated stimulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gating properties were also changed under A‐803467 with hyperpolarized steady‐state inactivation and delayed recovery from inactivation. Interestingly, the left‐shifted steady‐state inactivation was quite consistent with the effect of A‐803467 in isolated mouse intracardiac neurons delineated by Verkerk et al 36. Like other sodium channel blockers, our results support that A‐803467 might block sodium channels in an inactivated state and the number of trapped inactivated sodium channels might be increased during repeated stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…There is an increased number of studies that focus on the relationship of SCN10A /Na v 1.8 with cardiac diseases. In spite of several disputes such as the expression of Na v 1.8 in the heart,36, 39 Na v 1.8 is critical in cardiac electrophysiology. Our previous study first reported 17 putative pathogenic SCN10A variants in 25 of 150 Brugada syndrome probands with a positive proband yield of 16.7%, approaching our historical yield of 20.1% for SCN5A .…”
Section: Discussionmentioning
confidence: 99%
“…16 In cardiac myocytes, block of Nav1.8 reduces late Na C current and shortens action potential duration, 17 while block of Nav1.8 in intracardiac neurons reduces action potential frequency. 18 How these observations relate to cardiac conduction is not entirely clear. The picture is further complicated by the findings that SCN10A knock-out mice display a decreased PR interval, while pharmacological inhibition of Nav1.8 causes PR prolongation.…”
Section: Sodium Channelsmentioning
confidence: 99%
“…27) It is characterized by a long-duration action potential and preservation of excitability during rapid and sustained stimulation. SC-N10A has been recently identified in the human heart [28][29][30] and has been associated in GWAS with alterations in cardiac conduction, especially atrioventricular conduction (PR interval).…”
Section: Discussionmentioning
confidence: 99%